Aroma compounds and sensory characteristics as biomarkers of quality of differently processed Tunisian virgin olive oils. (4th May 2015) - Issaoui, Manel; Gharbi, Ines; Flamini, Guido; Cioni, Pier Luigi; Bendini, Alessandra; Gallina Toschi, Tullia; Hammami, Mohamed
Summary The influence of the extraction system (continuous vs. discontinuous) and the degree of freshness of olives on the chemical composition and the quality of Chemlali and Chétoui virgin olive oil has been studied. Analytical data mainly concerning the volatile and sensory profiles revealed statistically significant differences in relation to the extraction system. All quality indices and sensory characteristics showed statistically significant differences associated with the degree of freshness of fruits. These results further confirm the general consensus that volatile compounds can be very useful as biomarkers of the quality of virgin olive oil and show correlations with the sensory characteristics.